ENCYCLOPAEDIA BRITANNICA - Ashmore, Harry S. (edición) (WILLIAM BENTON, 1963)
CONTENIDO: V. 1 A TO ANTARAH. -- V. 2 ANTARCTICA TO BALFE.-- V. 3 BALFOUR TO BOTH. -- V. 4 BOTHA TO CARTHAGE. -- V. 5 CARTHUSIANS TO COCKCROFT. -- V. 6 COCKER TO DAIS. -- V. 7DAISY TO EDUCATIONAL PSYCHOLOGY. -- V. 8 EDWARD TO EXTRACT. -- V. 9 EXTRADITION TO GAMBRINUS. -- V. 10 GAME BIRDS TO GUITTONE. -- V. 11 GUIZOT TO HYDROXYLAMINE. -- V. 12 HYDROZOA TO JEREMY, EPISTLE OF. -- V. 13 JEREZ DE LA FRONTERA TO LIBERTY PARTY. -- V. 14 LIBIDO TO MARY, DUCHESS OF BURGUNDY. -- V. 15 MARYBOROUGH TO MUSHET STEEL. -- V. 16 MUSHROOM TO OZONOLYSIS. -- V. 17 P TO PLANT QUARANTINE. -- V. 18 PLANTS TO RAYMUND OF TRIPOLI. -- V. 19 RAYNAL TO SARRAUT. -- V.20 SARSAPARILLA TO SORCERY. -- V. 21 SORDELLO TO TEXTBOOKS. -- V. 22 TEXTILE TO VASCULAR SYSTEM. -- V. 23 VASE TO ZYGOTE. -- V. 24 INDEX